Semi-Empirical Haken-Strobl Model for Molecular Spin Qubits - Herrera-Urbina, F; Aravena-Ponce, D; Aravena-Ponce, D (Institute of Physics, 2023)
Understanding the physical processes that determine the relaxation T 1 and dephasing T 2 times of molecular spin qubits is critical for envisioned applications in quantum metrology and information processing. Recent spin-echo measurements of solid-state molecular spin qubits have stimulated the development of quantum mechanical models for predicting intrinsic qubit timescales using first-principles electronic structure methods. We develop an alternative semi-empirical approach to construct Redfield quantum master equations for molecular spin qubits using a stochastic Haken-Strobl theory for a central spin with fluctuating gyromagnetic tensor due to spin-lattice interaction and fluctuating local magnetic field due to interactions with lattice spins. Using two vanadium-based spin qubits as case studies, we compute qubit population and decoherence times as a function of temperature and magnetic field, using a bath spectral density parametrized with a small number of T 1 measurements. The theory quantitatively agrees with experimental data over a range of conditions beyond those used to parameterize the model, demonstrating the generalization potential of the method. The ability of the model to describe the temperature dependence of the ratio T 2 / T 1 is discussed and possible applications for designing novel molecule-based quantum magnetometers are suggested. © 2023 The Author(s). Published by IOP Publishing Ltd on behalf of the Institute of Physics and Deutsche Physikalische Gesellschaft.